W. C. Clark and the Politics of Canadian Housing Policy, 1935-1952 - Bacher, John (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1988)
To a remarkable extent the course of Canadian housing policy from 1935 to 1952 was set by the deputy minister of finance, W. C. Clark. By developing programs that stimulated the building of new homes for sale, he was able to deflect growing calls for a substantial federal program of subsidized low rental housing. Working in close consultation with representatives of mortgage-lending institutions, including D'Arcy Leonard, and with David Mansur, inspector of mortgages for Sun Life and later president of Central Mortgage and Housing Corporation, Clark was able to build an alliance of realty interests, home builders, life insurance companies, and material supply companies, such as retail lumber dealers. This alliance prevailed over public-housing supporters: trade unions, large construction companies, architects, social workers and urban planners. Clark was largely responsible for drafting the Dominion Housing Act of 1935 and the national housing acts of 1938 and 1944. Although all his legislation was geared to building new homes, and reducing political criticism, these acts also contained misleading and unworkable provisions for low-income housing. During World War II Clark reluctantly accepted rent-control and federal rental housing, but he restricted their scope and oversaw their phasing out by his long-time associate Mansur. Clark was also crucial in developing government programs that fostered large residential builders to plan future urban communities.